2009
DOI: 10.1177/1555412009351261
|View full text |Cite
|
Sign up to set email alerts
|

‘‘Blacks Deserve Bodies Too!’’: Design and Discussion About Diversity and Race in a Tween Virtual World

Abstract: In this paper, we investigate racial diversity in avatar design and public discussions about race within a large-scale tween virtual world called Whyville.net, with more than 1.5 million registered players of ages 8-16. One unique feature of Whyville is the player's ability to customize their avatars with various face parts and accessories, all designed and sold by other players in Whyville. Our findings report on the racial diversity of available resources for avatar construction and online postings about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 14 publications
1
50
0
1
Order By: Relevance
“…Lastly, while not surprising, the problematic representation of race in games has been a recurring topic in game studies literature [4,16,18,21]. This topic ranges from issues of lack of ethnic diversity in games and virtual worlds [16,18], problematic (often racist) representations of race in games [21], and the seemingly benign design decision to have character creation interfaces "default" to a particular ethnicity [4].…”
Section: Socially In/exclusive Interface Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, while not surprising, the problematic representation of race in games has been a recurring topic in game studies literature [4,16,18,21]. This topic ranges from issues of lack of ethnic diversity in games and virtual worlds [16,18], problematic (often racist) representations of race in games [21], and the seemingly benign design decision to have character creation interfaces "default" to a particular ethnicity [4].…”
Section: Socially In/exclusive Interface Designmentioning
confidence: 99%
“…This topic ranges from issues of lack of ethnic diversity in games and virtual worlds [16,18], problematic (often racist) representations of race in games [21], and the seemingly benign design decision to have character creation interfaces "default" to a particular ethnicity [4]. Mobilizing these and other critiques, we look to existing character creation interfaces to identify these common issues in a systematic manner and produce a set of best practices for the design of avatar creation interfaces in games.…”
Section: Socially In/exclusive Interface Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Humanity, these default features are distinctly Caucasian (Pace, 2008). WoW is not alone in this; prior research has noted a similar trend in the avatar construction of other cybercommunities (Kafai, Cook, & Fields, 2010;Nakamura, 2002). Avatars of color are given fewer options, and players are often left feeling as though they are merely playing White characters with dark skin (Pace, 2008).…”
Section: Variation Within the Human Racementioning
confidence: 82%
“…Furthermore, an analysis of avatar representations shows a systematic over-representation of males, Whites, and adults and an under-representation of females, Hispanics, Native Americans, children, and the elderly (Williams, Martins, Consalvo, & Ivory, 2009). Kafai, Cook, and Fields (2007) observed that in Whyville, a virtual world for youths aged 8Á16 years, players of color posted messages that complained about the lack of Black avatars or mismatched bodies, in which black-faced avatars had white bodies.…”
Section: Intercultural Dialectics and Identifications Onlinementioning
confidence: 99%